Working from Home, COVID-19 and Job Satisfaction - Inga Laß; Esperanza Vera-Toscano; Mark Wooden (Institute of Labor Economics (IZA), 2023)
This paper examines the impact of the growth in the incidence of working from home during the COVID-19 pandemic on workers' job satisfaction. Using longitudinal data collected in 2019 and 2021 as part of the Household, Income and Labour Dynamics in Australia (HILDA) Survey, fixed-effects models of job satisfaction are estimated. Changes in the share of total weekly work hours usually worked from home are not found to have any significant association with changes in job satisfaction for men. In contrast, a strong significant positive (but non-linear) association is found for women, and this relationship is concentrated on women with children. These findings suggest the main benefit of working from home for workers arises from the improved ability to combine work and family responsibilities, something that matters more to women given they continue to shoulder most of the responsibility for house and care work.
Keywords: J22; J28; 330; working from home; telework; job satisfaction; COVID-19; HILDA Survey; gender; work-family balance